Standardization of double blind placebo controlled food challenge with soy within a multicentre trial. Issue 1 (December 2016) - Treudler, R.; Franke, A.; Schmiedeknecht, A.; Ballmer-Weber, B.; Worm, M.; Werfel, T.; Jappe, U.; Biedermann, T.; Schmitt, J.; Brehler, R.; Kleinheinz, A.; Kleine-Tebbe, J.; et al.
Abstract Background Multicentre trials investigating food allergies by double blind placebo controlled food challenges (DBPCFC) need standardized procedures, challenge meals and evaluation criteria. We aimed at developing a standardized approach for identifying patients with birch related soy allergy by means of DBPCFC to soy, including determination of threshold levels, in a multicentre setting. Methods Microbiologically stable soy challenge meals were composed of protein isolate with consistent Gly m 4 levels. Patients sensitized to main birch allergen Bet v 1 and concomitant sensitization to its soy homologue Gly m 4 underwent DBPCFC. Outcome was defined according to presence and/or absence of ten objective signs and intensity of eight subjective symptoms as measured by visual analogue scale (VAS). Results 138 adult subjects (63.8% female, mean age 38 years) underwent DBPCFC. Challenge meals and defined evaluation criteria showed good applicability in all centres involved. 45.7% presented with objective signs and 65.2% with subjective symptoms at soy challenge. Placebo challenge meals elicited non-cardiovascular objective signs in 11.6%. In 82 (59.4%) subjects DBPCFC was judged as positive. 70.7% of DPBCFC+ showed objective signs and 85.4% subjective symptoms at soy challenge. Subjective symptoms to soy challenge meal in DBPCFC+ subjects started at significantly lower dose levels than objective signs (p < 0.001). Median cumulative eliciting doses for first objective signs in DBPCFC+ subjects were 4.7 g [0.7–24.7] and 0.7 g [0.2–4.7] total soy protein for first subjective symptoms (p = 0.01). Conclusions We present the hitherto largest group of adults with Bet v 1 and Gly m 4 sensitization being investigated by DBPCFC. In this type of food allergy evaluation of DBPCFC outcome should not only include monitoring of objective signs but also scoring of subjective symptoms. Our data may contribute to standardize DBPCFC in pollen-related food allergy in multicentre settings. Trial registration EudraCT: 2009-011737-27.